2015
DOI: 10.3892/mmr.2015.3367
|View full text |Cite
|
Sign up to set email alerts
|

Klotho gene delivery ameliorates renal hypertrophy and fibrosis in streptozotocin-induced diabetic rats by suppressing the Rho-associated coiled-coil kinase signaling pathway

Abstract: The present study aimed to investigate whether klotho gene delivery attenuated renal hypertrophy and fibrosis in streptozotocin-induced diabetic rats. A recombinant adeno-associated virus (rAAV) carrying mouse klotho full-length cDNA (rAAV.mKL), was constructed for in vivo investigation of klotho expression. Diabetes was induced in rats by a single tail vein injection of 60 mg/kg streptozotocin. Subsequently, the diabetic rats received an intravenous injection of rAAV.mKL, rAAV.green fluorescent protein (GFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Our previous study had also demonstrated that FGF1 treatment blocks ER stress and consequently apoptosis of DA neuron during development of Parkinson's disease (PD) . Moreover, FGF23, the FGF family, has also an anti‐oxidative stress activity . Thus, we hypothesized that FGF1‐associated glucose decreases and subsequent reduction of cellular stress is the another potential cellular molecule mechanisms mediating FGF1 treatment forDN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study had also demonstrated that FGF1 treatment blocks ER stress and consequently apoptosis of DA neuron during development of Parkinson's disease (PD) . Moreover, FGF23, the FGF family, has also an anti‐oxidative stress activity . Thus, we hypothesized that FGF1‐associated glucose decreases and subsequent reduction of cellular stress is the another potential cellular molecule mechanisms mediating FGF1 treatment forDN.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, FGF23, the FGF family, has also an anti-oxidative stress activity. 18,19 Thus, we hypothesized that FGF1-associated glucose decreases and subsequent reduction of cellular stress is the another potential cellular molecule mechanisms mediating FGF1 treatment forDN.…”
mentioning
confidence: 99%
“…Expression of klotho via adeno-associated virus gene delivery downregulated ROCK1 activity and reduced fibrosis in the streptozotocin-induced diabetes rat model (Deng et al, 2015). Increased klotho staining was seen in tubular epithelial cells, suggesting that the protective effect involved these cells; however, renal function was not assessed in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…AAV vectors designed for expression of suppressor of cytokine signaling (SOCS)2 over-expressed SOCS2 in the kidney and inhibited renal fibrosis and inflammation in a rat model of diabetic nephropathy [42]. The inhibitory effects on renal fibrosis by modulation of expression of the following genes by exogenous genes delivered with AAV vectors have been reported: adrenomedullin [43]; endothelial nitric oxide synthase [44]; Klotho [45]; cytochrome P450 2J2 [46]; and angiotensin II receptor 1 [47]. …”
Section: Viral and Non-viral Vectors For Renal Fibrosis In Vivomentioning
confidence: 99%